Vliv oxidativního stresu na telomerickou délku u Drosophila melanogaster - Szakosová, Klára (Jihočeská univerzita, 2015)
Oxidative stress is caused by an imbalance between high production of reactive oxygen species and ability of organism to detoxify them or counteract their effects. The chromosomal ends telomeres - are specialized nucleoprotein structures protecting chromosome ends from DNA damage. Telomeres of Drosophila melanogaster are arrays of specific non-long terminal repeated (LTR) retrotransposons HeT-A, TART and TAHRE. This thesis evaluates effects of exposure of paraquat, which is a strong oxidative stress inducer, on telomere length and transcription activity in Drosophila.
Effect of oxidative stress on telomere lenght in Drosophila melanogaster
Keywords: D. melanogaster; telomery; parakvat; oxidativní stres; D. melanogaster; telomeres; paraquat; oxidative stress